A high holding force balanced anchor and a method for manufacturing the same

CN122979765APending Publication Date: 2026-10-27RUGAO SENXUAN SHIP PARTS CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611376361.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-07
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

然而,现有技术对所有部位采用相同的化学成分和相同的热处理工艺,导致材料性能“一刀切”,无法根据各部位的受力特点进行针对性的性能优化

Benefits of technology

1.通过锚杆与锚爪的差异化合金成分设计,锚杆采用中低碳+Ni+Mo成分体系保证高强韧,锚爪采用中碳+Cr+V成分体系保证高硬耐磨,实现了不同部位性能的精准匹配,避免了“一刀切”的性能浪费或性能不足。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122979765A_ABST
    Figure CN122979765A_ABST
Patent Text Reader

Abstract

The application relates to a large-grabbing-force balanced anchor and a preparation method thereof, and belongs to the technical field of ship anchoring equipment. The large-grabbing-force balanced anchor comprises an anchor rod and an anchor jaw. The anchor rod is made of a first alloy steel, and the anchor jaw is made of a second alloy steel. The carbon content in the first alloy steel is 0.12-0.18 wt%, the nickel content is 0.40-0.70 wt%, and the molybdenum content is 0.15-0.30 wt%. The carbon content in the second alloy steel is 0.18-0.25 wt%, the chromium content is 0.50-1.00 wt%, and the vanadium content is 0.05-0.12 wt%. The anchor rod is quenched and high-temperature tempered to obtain a tempered sorbite structure, the yield strength is greater than or equal to 450 MPa, and the impact absorption energy at-20 DEG C is greater than or equal to 60 J. The anchor jaw is quenched and medium-temperature tempered to obtain a tempered sorbite structure, the surface hardness is greater than or equal to HB220, and the impact absorption energy at-20 DEG C is greater than or equal to 34 J. Through the differential component design and the differential heat treatment process of the anchor rod and the anchor jaw, the high strength and toughness of the anchor rod and the high hardness and wear resistance of the anchor jaw are cooperatively matched.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of ship anchoring equipment technology, and in particular to a high-holding-force balanced anchor and its preparation method. Background Technology

[0002] A high-holding-capacity balancing anchor is a special marine anchor with rotating anchor claws. It consists of components such as anchor bolts, anchor claws, pins, cross pins, end caps, and anchor shackles, and is widely used in positioning and mooring systems for large ships, offshore platforms, and floating installations.

[0003] Currently, high-holding-force balanced anchors are mainly manufactured using casting or forging processes, with ordinary carbon structural steel or low-alloy cast steel as the primary materials. The national standard GB / T548-1996, "Technical Conditions for Anchors," stipulates that the yield strength of cast steel anchor parts should be ≥200MPa, and the tensile strength ≥400MPa. Industry standards uniformly require that the chemical composition of anchor bolts, anchor claws, and other components be C≤0.23%, Mn0.50~1.60%, and the total residual elements ≤0.80%.

[0004] However, existing high-holding-force balancing anchors suffer from the following technical problems in terms of materials and processes: different parts experience significantly different stress states, yet the material performance requirements are uniform. In practical use, the anchor bolt primarily bears tensile and bending loads, requiring high strength and toughness; the anchor claws need to withstand impacts and abrasion from the seabed, requiring high hardness and wear resistance; and the pins and hinges need to withstand shear and alternating loads, requiring high fatigue strength and surface hardness. However, existing technologies use the same chemical composition and heat treatment process for all parts, resulting in a "one-size-fits-all" approach to material performance, making it impossible to optimize performance specifically for the stress characteristics of each part. Summary of the Invention

[0005] To address the aforementioned issues, this application provides a high-holding-force balanced anchor and its preparation method.

[0006] This application provides a high-holding-force balanced anchor and its manufacturing method, which adopts the following technical solution: A high-holding-force balanced anchor includes an anchor rod and anchor claws connected to the anchor rod. The anchor rod is made of a first alloy steel, and the anchor claws are made of a second alloy steel. The first alloy steel contains 0.12~0.18 wt% carbon, 1.00~1.50 wt% manganese, 0.40~0.70 wt% nickel, and 0.15~0.30 wt% molybdenum. The second alloy steel contains 0.18~0.25 wt% carbon, 1.20~1.80 wt% manganese, 0.50~1.00 wt% chromium, and 0.05~0.12 wt% vanadium. The anchor rod has a yield strength ≥450 MPa, and the anchor claws have a surface hardness ≥HB220.

[0007] By adopting the above technical solutions, the anchor bolt and anchor claw are designed with differentiated alloy compositions to meet the service performance requirements of different parts. For the first alloy steel used in the anchor bolt, the carbon content is controlled in the low-to-medium carbon range of 0.12~0.18wt%, ensuring good weldability and low-temperature toughness; the nickel content is 0.40~0.70wt%, nickel is a key element for improving low-temperature toughness, which can lower the ductile-brittle transition temperature of steel and ensure that the anchor bolt can still maintain good impact resistance in cold sea areas (-20℃); the molybdenum content is 0.15~0.30wt%, molybdenum can improve the hardenability of steel and refine the grain, while enhancing tempering stability, so that the anchor bolt can still maintain sufficient strength after high-temperature tempering. For the second alloy steel used for anchor claws, the carbon content is increased to 0.18~0.25wt%, and the higher carbon content is beneficial to improving hardenability and surface hardness; the chromium content is 0.50~1.00wt%, chromium is an effective element to improve wear resistance, can form stable carbides and increase the electrode potential of the matrix, and enhance the resistance to seawater corrosion; the vanadium content is 0.05~0.12wt%, vanadium produces precipitation strengthening effect by forming fine VC precipitates and refines austenite grains, improving strength without significantly impairing toughness.

[0008] This technical solution breaks through long-standing technical biases in the field of ship anchor manufacturing. Those skilled in the art have long believed that using the same material for all parts of the anchor simplifies smelting, casting, and heat treatment processes, reducing production costs. Furthermore, standards such as GB / T548 and CB / T430 uniformly specify the chemical composition requirements for all components. However, the inventors recognize that the service conditions of anchor bolts and anchor claws are fundamentally different: anchor bolts withstand axial tensile and bending stresses, with failure modes including overload fracture or low-temperature brittle fracture; anchor claws withstand the impact and abrasive wear of seabed sand and gravel, with failure modes including surface wear or impact cracking. These two failure modes have drastically different material performance requirements—the former requires high strength and high toughness, while the latter requires high hardness and a certain degree of toughness. Manufacturing anchor bolts and anchor claws using differentiated materials and heat treatments, while increasing the complexity of the production process, achieves precise design by "using the best steel where it's needed most," significantly improving the overall service life of the anchor.

[0009] Furthermore, the anchor bolt has an impact absorption energy of ≥60J at -20℃; the anchor claw has an impact absorption energy of ≥34J at -20℃.

[0010] By adopting the above technical solution, the toughness indicators of anchor bolts and anchor claws in low-temperature environments were clarified. The anchor bolt's impact absorption energy at -20℃ is ≥60J, far exceeding the standard requirement (usually ≥27J), ensuring that the anchor bolt will not experience low-temperature brittle fracture when operating in polar or cold-water areas; the anchor claw's impact absorption energy at -20℃ is ≥34J, maintaining the necessary low-temperature toughness while ensuring sufficient hardness, preventing the anchor claw from cracking under impact loads.

[0011] Furthermore, the nickel content in the first alloy steel is 0.40~0.70wt%, the nickel content in the second alloy steel is 0.20~0.40wt%, and the nickel content of the anchor rod is higher than that of the anchor claw.

[0012] By employing the above technical solution, nickel, a key alloying element for improving low-temperature impact toughness, is utilized, but it is expensive. Anchor bolts require high toughness, hence a higher nickel content; anchor claws prioritize hardness over toughness, thus requiring a lower nickel content. This differentiated design optimizes alloy costs while ensuring performance.

[0013] Furthermore, the microstructure of the anchor bolt is tempered sorbite, and the microstructure of the anchor claw is tempered troostite.

[0014] By adopting the above technical solutions, tempered sorbite, a microstructure formed after quenched martensite is tempered at high temperature, is characterized by a uniformly distributed fine-grained carbides on an equiaxed ferrite matrix, exhibiting excellent comprehensive mechanical properties—both high strength (yield strength ≥ 450 MPa) and excellent plasticity and low-temperature toughness, making it particularly suitable for anchor bolts subjected to tensile and bending loads. Tempered troostite, a microstructure formed after quenched martensite is tempered at medium temperature, consists of acicular ferrite that has not undergone recrystallization and fine carbides, possessing high hardness and wear resistance while retaining a certain degree of toughness, making it particularly suitable for anchor claws subjected to impact wear. This application precisely controls the formation of these two microstructures by controlling the tempering temperature, enabling both anchor bolts and anchor claws to obtain optimal microstructures.

[0015] Furthermore, the anchor rod and the anchor claw are fixedly connected by welding, threaded connection or pin connection.

[0016] By adopting the above technical solutions, multiple connection methods are provided, which can be flexibly selected according to the specific structural design and manufacturing conditions of the anchor.

[0017] A method for preparing a high-holding-force balanced anchor includes the following steps: Step S1: Melting and casting according to the composition ratio of a first alloy steel to obtain an anchor rod casting; Step S2: Melting and casting according to the composition ratio of a second alloy steel to obtain an anchor claw casting; Step S3: Quenching and high-temperature tempering treatment on the anchor rod casting, with a quenching temperature of 840~890℃ and a tempering temperature of 580~650℃; Step S4: Quenching and medium-temperature tempering treatment on the anchor claw casting, with a quenching temperature of 840~890℃ and a tempering temperature of 450~550℃; Step S5: Assembling the heat-treated anchor rod and anchor claw to obtain a high-holding-force balanced anchor.

[0018] By adopting the above technical solution, steps S1 and S2 involve melting and casting with differentiated compositions to ensure that the chemical composition of the anchor rod and anchor claw meets the performance requirements. In step S3, the anchor rod undergoes quenching followed by high-temperature tempering to obtain a tempered sorbite structure, achieving the optimal match between strength and toughness. In step S4, the anchor claw undergoes quenching followed by medium-temperature tempering to obtain a tempered troostite structure, ensuring a surface hardness ≥ HB220. Step S5 assembles the separately heat-treated anchor rod and anchor claw into a finished product. This method breaks with the existing technical convention of using the same heat treatment process for both anchor rod and anchor claw. By using differentiated heat treatment, the same quenched martensite transforms into different structures at different tempering temperatures, thereby achieving precise performance control in different parts of the same anchor.

[0019] Furthermore, in step S3, the anchor rod is quenched and then tempered at high temperature to obtain a microstructure mainly composed of tempered sorbite; in step S4, the anchor claw is quenched and then tempered at medium temperature to obtain a microstructure mainly composed of tempered troostite, and the surface hardness of the anchor claw reaches HB220 or higher.

[0020] Furthermore, in step S3, the tempering temperature of the anchor rod is 600~650℃; in step S4, the tempering temperature of the anchor claw is 480~520℃. Within this preferred temperature range, the anchor rod can obtain a more uniform tempered sorbite structure, and the hardness and toughness of the anchor claw achieve an optimal balance.

[0021] Furthermore, in steps S1 and S2, the melting temperature is 1580~1650℃, and the pouring temperature is 1520~1580℃. This melting temperature range ensures the full dissolution of alloying elements and the homogenization of the molten steel, while the pouring temperature ensures the integrity of the casting and the dimensional accuracy of the dimensions.

[0022] Furthermore, it also includes a surface treatment step: the assembled anchor is subjected to overall surface anti-corrosion treatment, which is thermal spraying of zinc, aluminum or zinc-aluminum alloy coating, or coating with epoxy zinc-rich primer + epoxy micaceous iron oxide intermediate paint + polyurethane topcoat.

[0023] By adopting the above technical solutions, the corrosion resistance of anchors in marine environments has been effectively improved, and their service life has been extended.

[0024] In summary, this application includes at least one of the following beneficial effects: 1. By designing differentiated alloy compositions for the anchor bolt and anchor claw, the anchor bolt adopts a low-to-medium carbon + Ni + Mo composition system to ensure high strength and toughness, while the anchor claw adopts a medium carbon + Cr + V composition system to ensure high hardness and wear resistance. This achieves precise matching of performance in different parts, avoiding the waste or inadequacy of performance through a "one-size-fits-all" approach.

[0025] 2. By using differentiated heat treatment processes such as anchor bolt quenching + high-temperature tempering and anchor claw quenching + medium-temperature tempering, tempered sorbite and tempered troostite structures are obtained respectively, resulting in anchor bolt yield strength ≥450MPa and impact energy ≥60J at -20℃, and anchor claw surface hardness ≥HB220 and impact energy ≥34J at -20℃. The overall performance is significantly better than the requirements of existing standards.

[0026] 3. By differentiating the nickel content, the nickel content in the anchor bolt is higher than that in the anchor claw, which optimizes the alloy cost while ensuring the hardness requirements of the anchor claw, and achieves a balance between performance and economy.

[0027] 4. By limiting the tempering temperature of the anchor bolt to 600~650℃ and the tempering temperature of the anchor claw to 480~520℃, the microstructure and performance matching of the two parts were further optimized, so that the plasticity and toughness of the anchor bolt were fully restored and the hardness of the anchor claw reached the optimal level.

[0028] 5. Surface anti-corrosion treatment effectively improves the corrosion resistance of anchors in marine environments. Attached Figure Description

[0029] Figure 1 This is a process flow diagram of the preparation method according to an embodiment of this application. Detailed Implementation

[0030] The present application will be further described in detail below with reference to the accompanying drawings.

[0031] This application discloses a high-grip balance anchor and its preparation method.

[0032] This application discloses a high-holding-force balanced anchor, including an anchor rod and an anchor claw connected to the anchor rod. The anchor rod and the anchor claw are rotatably connected by a pin. An anchor shackle is provided at the top of the anchor rod, and the anchor rod and the anchor claw are fixed by a cross pin.

[0033] The anchor bolt is made of first alloy steel. The first alloy steel comprises, by weight percentage: 0.12~0.18wt% carbon, 1.00~1.50wt% manganese, 0.40~0.70wt% nickel, 0.15~0.30wt% molybdenum, with the balance being iron and unavoidable impurities. The anchor bolt has a yield strength ≥450MPa, a tensile strength ≥600MPa, and an impact absorption energy ≥60J at -20℃. The microstructure of the anchor bolt is tempered sorbite.

[0034] The anchor claws are made of a second alloy steel. The second alloy steel, by weight percentage, comprises: 0.18~0.25wt% carbon, 1.20~1.80wt% manganese, 0.50~1.00wt% chromium, 0.05~0.12wt% vanadium, and 0.20~0.40wt% nickel, with the balance being iron and unavoidable impurities. The surface hardness of the anchor claws is ≥HB220, and the impact absorption energy at -20℃ is ≥34J. The microstructure of the anchor claws is tempered troostite.

[0035] This application also provides a method for preparing the above-mentioned high-holding-force balanced anchor, referring to... Figure 1 This includes the following steps: Step S1: Melt and cast according to the composition ratio of the first alloy steel. Add scrap steel, pig iron, and alloys such as nickel plate and ferromolybdenum into a medium-frequency induction furnace and melt at 1580~1650℃. After the molten steel is fully deoxidized and refined, it is poured at 1520~1580℃ to obtain the anchor bolt casting.

[0036] Step S2: Melt and cast according to the composition ratio of the second alloy steel. Add scrap steel, pig iron, and alloys such as ferrochrome and ferrovanadium into a medium-frequency induction furnace and melt at 1580~1650℃. After the molten steel is fully deoxidized and refined, it is poured at 1520~1580℃ to obtain the anchor claw casting.

[0037] Step S3: Quench and temper the anchor bolt casting. The quenching temperature is 840~890℃, and the holding time is calculated based on the casting wall thickness of 1.5~2.0 min / mm. Cool to room temperature with water or oil. The tempering temperature is 580~650℃ (preferably 600~650℃), and the tempering time is 2~4 hours. Air cool to room temperature. After this process, the anchor bolt obtains a microstructure mainly composed of tempered sorbite.

[0038] Step S4: Quench and temper the anchor claw casting. The quenching temperature is 840~890℃, and the holding time is calculated based on the casting wall thickness of 1.5~2.0 min / mm. Cool to room temperature with water or oil. The tempering temperature is 450~550℃ (preferably 480~520℃), and the tempering time is 2~4 hours. Air cool to room temperature. After this process, the anchor claw obtains a microstructure mainly composed of tempered troostite, with a surface hardness reaching HB220 or higher.

[0039] Step S5: Assemble the heat-treated anchor rod and anchor claw, and fix them together with connecting parts such as pins and cross pins to obtain a high holding force balanced anchor.

[0040] Step S6 (optional): Perform overall surface anti-corrosion treatment on the assembled anchorage, using thermal spraying of zinc-aluminum alloy coating or coating with epoxy zinc-rich primer + epoxy micaceous iron oxide intermediate paint + polyurethane topcoat.

[0041] The above technical solution is verified through specific embodiments and comparative examples below.

[0042] Examples 1-10 and Comparative Examples 1-6 Table 1. Chemical composition (wt%) and heat treatment process of the examples and comparative examples

[0043] Test methods and standards 1. Yield strength: According to GB / T228.1-2010, take a Φ10mm standard tensile specimen and test it on a universal testing machine.

[0044] 2. Impact absorption energy at -20℃: According to GB / T229-2007, take a standard V-notch impact specimen of 10mm×10mm×55mm and test it on a low temperature impact testing machine at -20℃.

[0045] 3. Surface hardness: According to GB / T231.1-2018, a Brinell hardness tester was used with a load of 187.5 kg and an indenter diameter of 2.5 mm.

[0046] 4. Microstructure observation: According to GB / T13298-2015, after the sample is ground, polished, and etched with 4% nitric acid alcohol, it is observed under an optical microscope.

[0047] 5. Grain size: Rating according to GB / T6394-2017.

[0048] Performance test results Table 2 Performance test results of the examples and comparative examples

[0049] Data Analysis and Discussion I. Metallurgical Principles and Creative Analysis of Differentiated Composition Design The core innovation of this invention lies in breaking the long-standing technical convention in the anchor manufacturing field of "the same anchor, the same steel, and the same heat treatment." Existing technologies (such as standards GB / T548 and CN104451406A) all adopt a single-component design. The implicit technical logic is that all parts of the anchor are formed by integral casting, and using the same material can simplify the smelting, casting, and heat treatment processes to the greatest extent and reduce production costs. However, this technical logic ignores a crucial fact: the service conditions of different parts of a high-holding-force balanced anchor are fundamentally different, and this difference cannot be bridged by subsequent integral heat treatment.

[0050] From a metallurgical perspective, the main failure modes of anchor bolts are overload tensile fracture and low-temperature brittle fracture. Tensile fracture requires a high yield strength (≥450MPa), while low-temperature brittle fracture requires a low ductile-brittle transition temperature (impact energy ≥60J at -20℃). These two performance indicators are contradictory in steel: increasing strength usually requires increasing carbon content or alloying elements, but this leads to a decrease in toughness; increasing toughness usually requires reducing carbon content and adding expensive elements such as Ni, but this results in insufficient strength. Therefore, anchor bolt steel must achieve an optimal balance between strength and toughness.

[0051] The main failure modes of anchor claws are abrasive wear and impact cracking. Abrasive wear requires materials with high surface hardness (≥HB220), and hardness is positively correlated with carbon content; impact cracking requires materials with a certain degree of toughness (impact energy ≥34J at -20℃). Unlike anchor bolts, anchor claws have lower requirements for toughness than for hardness, therefore, different trade-offs can be made in carbon content compared to anchor bolts.

[0052] Based on the above analysis, this application adopts a composition system of medium-low carbon (0.12~0.18wt%) + Ni (0.40~0.70wt%) + Mo (0.15~0.30wt%) for the anchor bolt. The carbon content is controlled within a low range, providing a compositional basis for obtaining good low-temperature toughness after high-temperature tempering. Ni is the only element that can simultaneously improve strength and lower the ductile-brittle transition temperature. The mechanism is that Ni can increase stacking fault energy, promote cross-slip, and allow dislocations to move even at low temperatures, thereby delaying the occurrence of physical fracture. Mo can improve the hardenability of steel, ensuring that large-section anchor bolts obtain a fully martensitic structure after quenching. Simultaneously, Mo carbides can refine the grains during high-temperature tempering.

[0053] The anchor claws are constructed using a composition system of medium carbon (0.18~0.25wt%) + Cr (0.50~1.00wt%) + V (0.05~0.12wt%). The carbon content is slightly higher than that of the anchor rod to improve hardenability and surface hardness. Cr forms (Fe,Cr)3C carbides, increasing the electrode potential of the matrix and enhancing seawater corrosion resistance. Simultaneously, the high hardness of Cr carbides improves wear resistance. V generates precipitation strengthening by forming nanoscale VC precipitates, and at the austenitizing temperature, undissolved VC particles can pin grain boundaries, refining austenite grains, thus increasing hardness without significantly compromising toughness.

[0054] The ingenuity of this differentiated composition design lies in the fact that, in the prior art, those skilled in the art generally believe that using the same material for the same anchor is more economical and reasonable (a typical technological bias). However, the inventors, through systematic analysis of different failure modes of the anchor rod and anchor claw, designed two different alloy composition systems, enabling the anchor rod to achieve a high strength and toughness, and the anchor claw to achieve a high hardness and wear resistance. Although this increases the complexity of the smelting and casting processes, it significantly improves the overall service life and safety of the anchor.

[0055] II. Technical Principles and Creative Analysis of Differentiated Heat Treatment Processes Another ingenious aspect of this invention lies in employing different heat treatment processes for the anchor bolt and anchor claw. In the prior art, various parts of the same anchor are typically subjected to integral heat treatment in the same furnace to simplify the production process. However, the technical drawback of this approach is that the microstructure transformation path and final properties of quenched martensite are completely different when tempered at different temperatures.

[0056] Specifically, when quenched martensite is tempered at 150–250℃, supersaturated carbon atoms in the martensite segregate towards dislocations and grain boundaries, forming ε-carbides. At this stage, the microstructure is tempered martensite, which has the highest hardness but very poor toughness. When tempered at 350–500℃, the ε-carbides transform into fine cementite (Fe3C), and the acicular morphology of the martensite gradually disappears but is not yet fully recrystallized. At this stage, the microstructure is tempered troostite, which has high hardness and some toughness. When tempered at 550–650℃, the cementite further aggregates and spheroidizes, and the ferrite matrix undergoes recovery and recrystallization, forming an equiaxed ferrite + spheroidal carbide microstructure, i.e., tempered sorbite. At this stage, the strength is moderate, but the toughness and plasticity are optimal.

[0057] This application sets the tempering temperature of the anchor bolt to 580~650℃ (preferably 600~650℃) to fully transform the quenched martensite into tempered sorbite, achieving the best strength-toughness match; and sets the tempering temperature of the anchor claw to 450~550℃ (preferably 480~520℃) to transform the quenched martensite into tempered troostite, achieving sufficient low-temperature toughness (-20℃ impact energy ≥34J) while maintaining high hardness (HB≥220).

[0058] Comparative Examples 5 and 6 fully demonstrate the technical fact that differentiated heat treatments are not interchangeable. In Comparative Example 5, the anchor claw was mistakenly tempered at high temperature (620℃), resulting in a microstructure that transformed into tempered sorbite with a surface hardness of only HB190, failing to meet the requirement of ≥HB220 for the anchor claw. This insufficient hardness would cause the anchor claw to wear rapidly during service. In Comparative Example 6, the anchor rod was mistakenly tempered at medium temperature (500℃), resulting in a microstructure that transformed into tempered troostite. Although the yield strength was as high as 530MPa, the impact energy at -20℃ was only 35J, failing to meet the requirement of ≥60J for the anchor rod. This posed a risk of low-temperature brittle fracture in cold sea areas. These two comparative examples demonstrate from the opposite perspective that anchor rods must be tempered at high temperature to obtain tempered sorbite, while anchor claws must be tempered at medium temperature to obtain tempered troostite; the two are not interchangeable or substitutes.

[0059] III. Mechanism Analysis of Performance Comparison between Examples and Comparative Examples Example 1 (differentiated composition + differentiated heat treatment): The anchor bolt has a yield strength of 485 MPa and an impact energy of 68 J at -20℃; the anchor claw has a hardness of HB235 and an impact energy of 38 J at -20℃. All indicators meet the design requirements. Comparative Example 1 (ordinary carbon steel + same heat treatment): The anchor bolt and anchor claw have a yield strength of only 320 MPa and an impact energy of only 25 J at -20℃. This comparison shows that even after heat treatment, ordinary carbon steel cannot meet the high requirements for anchor bolt strength and toughness, and its hardness cannot meet the wear resistance requirements for anchor claws.

[0060] Comparative Example 2 (tempering temperature too low) exhibits high strength and hardness (anchor bolt yield strength 560 MPa, anchor claw hardness HB285), but severely insufficient toughness (anchor bolt impact energy only 28 J, anchor claw only 20 J). The mechanism lies in the incomplete decomposition of martensite during tempering at 420℃, resulting in the precipitation of carbides in needle-like or lamellar form. The coherent relationship with the matrix is ​​not fully disrupted. This microstructure possesses extremely high hardness but extremely low toughness, making it prone to brittle fracture under impact loads.

[0061] Comparative Example 3 (tempering temperature too high) exhibited excellent toughness (anchor bolt 80J, anchor claw 55J), but its strength and hardness decreased significantly (anchor bolt yield strength 380MPa, anchor claw hardness HB185). The mechanism is that during tempering at 700℃ / 600℃, carbides severely aggregated and coarsened, the ferrite matrix completely recrystallized, and the microstructure approached tempered pearlite, thus losing the strengthening effect brought by the martensitic transformation.

[0062] Example 4 (preferred tempering temperature: 600℃ for anchor bolt and 480℃ for anchor claw) is a further optimization based on Example 1. The impact energy of the anchor bolt is increased to 72J (an increase of 5.9%), and the hardness of the anchor claw is increased to HB240 (an increase of 2.1%). This shows that within the preferred temperature range, the toughness of the anchor bolt is more fully restored, and the hardness of the anchor claw reaches a better level.

[0063] Example 3 (high alloy content): The anchor bolt yield strength reached 510 MPa, and the anchor claw hardness reached HB248, all of which were at their highest levels. However, the higher alloy content increased the material cost. Example 2 (low alloy content): Although the indicators were slightly lower, they still met the design requirements and were suitable for cost-sensitive applications.

[0064] IV. Optimal Overall Performance Solution Example 1 achieves the optimal balance between the anchor bolt yield strength (485MPa), -20℃ impact energy (68J), and the anchor claw hardness (HB235), -20℃ impact energy (38J). All indicators meet the design requirements with sufficient margin, making it the optimal implementation scheme. Example 4, at the preferred temperatures of 600℃ tempering for the anchor bolt and 480℃ tempering for the anchor claw, further increases the anchor bolt impact energy to 72J and the anchor claw hardness to HB240, resulting in superior overall performance. It is suitable for polar vessels requiring higher low-temperature toughness and wear resistance.

[0065] Summary of Implementation Principles The implementation principle of the high-holding-force balancing anchor in this application embodiment is as follows: Based on the service characteristics of the anchor rod, which mainly bears tensile and bending loads, a medium-low carbon + Ni + Mo alloy composition system is adopted. Through quenching and high-temperature tempering (580~650℃), a tempered sorbite structure is obtained, giving the anchor rod both high strength (yield strength ≥ 450MPa) and excellent low-temperature toughness (impact energy ≥ 60J at -20℃). Based on the service characteristics of the anchor claw, which needs to withstand seabed impact and wear, a medium carbon + Cr + V alloy composition system is adopted. Through quenching and medium-temperature tempering (450~550℃), a tempered troostite structure is obtained, giving the anchor claw both high surface hardness (HB ≥ 220) and sufficient low-temperature toughness (impact energy ≥ 34J at -20℃). These two differentiated designs enable precise performance matching in different parts of the balancing anchor, breaking the long-standing "one-size-fits-all" technical bias in the anchor manufacturing field and significantly improving the overall service life and safety of the balancing anchor.

[0066] The above description is merely a preferred embodiment of this application and is not intended to limit this application. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of this application should be included within the protection scope of this application.

Claims

1. A high-holding-force balanced anchor, comprising an anchor bolt and anchor claws connected to the anchor bolt, characterized in that: The anchor bolt is made of a first alloy steel, and the anchor claw is made of a second alloy steel; In the first alloy steel, the carbon content is 0.12~0.18wt%, the manganese content is 1.00~1.50wt%, the nickel content is 0.40~0.70wt%, and the molybdenum content is 0.15~0.30wt%. In the second alloy steel, the carbon content is 0.18~0.25wt%, the manganese content is 1.20~1.80wt%, the chromium content is 0.50~1.00wt%, and the vanadium content is 0.05~0.12wt%. The yield strength of the anchor bolt is ≥450MPa, and the surface hardness of the anchor claw is ≥HB220.

2. The high-holding-force balanced anchor according to claim 1, characterized in that, The anchor bolt has an impact absorption energy of ≥60J at -20℃; the anchor claw has an impact absorption energy of ≥34J at -20℃.

3. The high-holding-force balanced anchor according to claim 1, characterized in that, The first alloy steel has a nickel content of 0.40~0.70wt%, the second alloy steel has a nickel content of 0.20~0.40wt%, and the nickel content of the anchor bolt is higher than that of the anchor claw.

4. The high-holding-force balanced anchor according to claim 1, characterized in that, The microstructure of the anchor bolt is tempered sorbite, and the microstructure of the anchor claw is tempered troostite.

5. The high-holding-force balanced anchor according to claim 1, characterized in that, The anchor rod and anchor claw are fixedly connected by welding, threaded connection or pin connection.

6. A method for preparing a high-holding-force balanced anchor according to any one of claims 1 to 5, characterized in that, Includes the following steps: Step S1: Melt and cast according to the composition ratio of the first alloy steel to obtain the anchor casting; Step S2: Melt and cast according to the composition ratio of the second alloy steel to obtain the anchor claw casting; Step S3: Quenching and high-temperature tempering are performed on the anchor bolt casting. The quenching temperature is 840~890℃ and the tempering temperature is 580~650℃. Step S4: Quench and temper the anchor claw casting at a medium temperature. The quenching temperature is 840~890℃ and the tempering temperature is 450~550℃. Step S5: Assemble the heat-treated anchor rod and anchor claw to obtain a high holding power balanced anchor.

7. The preparation method according to claim 6, characterized in that, In step S3, the anchor rod is quenched and then tempered at high temperature to obtain a microstructure mainly composed of tempered sorbite; in step S4, the anchor claw is quenched and then tempered at medium temperature to obtain a microstructure mainly composed of tempered troostite, and the surface hardness of the anchor claw reaches HB220 or higher.

8. The preparation method according to claim 6, characterized in that, In step S3, the tempering temperature of the anchor rod is 600~650℃; in step S4, the tempering temperature of the anchor claw is 480~520℃.

9. The preparation method according to claim 6, characterized in that, In steps S1 and S2, the melting temperature is 1580~1650℃ and the casting temperature is 1520~1580℃.

10. The preparation method according to claim 6, characterized in that, It also includes a surface treatment step: the assembled anchor is subjected to overall surface anti-corrosion treatment, which is thermal spraying of zinc, aluminum or zinc-aluminum alloy coating, or coating with epoxy zinc-rich primer + epoxy micaceous iron oxide intermediate paint + polyurethane topcoat.

Citation Information

Patent Citations

  • Highly saline-alkaline corrosion resistant stainless steel casting and preparation method thereof

    CN104451406A